2011
DOI: 10.1038/ijir.2011.43
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curculigo orchioides on hyperglycemia-induced oligospermia and sexual dysfunction in male rats

Abstract: Sustained hyperglycemia is considered as a major cause of sexual and erectile dysfunction in human population. Curculigo orchioides (CO) is considered as a sexual tonic in Ayurvedic system of medicine with potent antioxidant and adaptogenic properties. The aqueous extract of the herb was evaluated for its effectiveness against streptozotocin-induced hyperglycemic stress and subsequent sexual dysfunction due to hyperglycemia in male rats. Six groups with eight male rats in each group were used for this study an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…WankeuNya et al (2014) have reported significant decreases in mount, intromission and ejaculatory latencies after 4 weeks of treatment of T1 diabetic rats with root bark extract of Dracaena arborea. Curculigo orchioides extract significantly decreases mount, intromission and ejaculatory latencies and frequencies in T1 diabetes, (Thakur et al, 2012). Similarly, rutin significantly reduces mount, intromission and ejaculatory latencies, and increases their frequencies (Al-Roujeaie et al, 2016).…”
Section: Natural Products With Post-testicular Beneficial Effects In mentioning
confidence: 96%
See 1 more Smart Citation
“…WankeuNya et al (2014) have reported significant decreases in mount, intromission and ejaculatory latencies after 4 weeks of treatment of T1 diabetic rats with root bark extract of Dracaena arborea. Curculigo orchioides extract significantly decreases mount, intromission and ejaculatory latencies and frequencies in T1 diabetes, (Thakur et al, 2012). Similarly, rutin significantly reduces mount, intromission and ejaculatory latencies, and increases their frequencies (Al-Roujeaie et al, 2016).…”
Section: Natural Products With Post-testicular Beneficial Effects In mentioning
confidence: 96%
“…Vignon et al (1990) have previous reported a significant increase in sperm concentration in TIDM patients, while Garcia-Diez (1991) has reported a significant decrease in sperm count, motility and percentage of spermatozoa with normal morphology. However, Agbaje et al (2007) have found an insignificant increase in sperm concentration and total sperm output with an insignificant decrease in sperm motility, and normal sperm morphology.…”
Section: Effect Of Diabetes Mellitus On Spermatogenesismentioning
confidence: 99%
“…Hyperglycemia elicits plentiful biochemical pathways, viz. activation of the polyol pathway, mitogen-activated protein kinase pathway, formation of advanced glycation end products (AGEs) with subsequent activation of AGEs, and inducible nitric oxide receptor (Kishore et al, 2018;Oates, 2002;Singh et al, 2015;Smith, 2012;Toth et al, 2008). Excessive stimulation of the polyol pathway is deleterious, primarily by increasing the yield of cofactors such as reduced nicotinamide adenine dinucleotide phosphate and nicotinamide adenine dinucleotide (NAD+), which leads to a reduced level of glutathione as well as increased AGEs formation, activation of protein kinase-C (PKC), and diacylglycerol pathway (Adisakwattana et al, 2012;Singh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many Indian medicinal plants have been used to increase sexual function in men, but their mechanisms of action are not clearly known. Studies conducted within last decade using animal models, tried to elucidate the mechanisms of actions of few aphrodisiac plants (Sharma et al , ; Thakur et al , ; Sharma et al , ; Sharma et al , ; Chauhan et al , ; Chauhan et al , ; Goswami et al , ; Goswami et al , ). Apart from their effect on sEH, plant extracts are also reported to increase sexual function by increasing level of testosterone or by inhibiting enzymes like arginase, rho‐kinase, PDE5, and sEH (Andersson, ; Goswami et al , ; Goswami et al , ; Yousif and Benter, ).…”
Section: Introductionmentioning
confidence: 99%